Mapping of aquifer hydraulic properties in Ogbeje and Umeghe in Abraka, Delta State Nigeria: insights from geophysical and hydrogeological methods (Journal of Tropical Resources and Sustainable Science (JTRSS), 2022)
Vertical Electrical Sounding (VES), Pumping test, well logging and grain size analysis were conducted with the aim of studying the subsurface geophysical formation in order to determine aquifer characteristics such as hydraulic conductivity, transmissivity and other parameters for groundwater exploration purposes around Ogbeje and Umeghe, Abraka Delta State. Nine (9) VES stations were occupied and the results obtained from the computer iterations suggest 4 to 5 geoelectric layers. The aquiferous layers wwerefound at a depth ranging from 20.0 m – 38.3 m with resistivity ranging from 2200 ?m to 8500 ?m and thickness varying between 6.7 and 20.0 m. The VES study reveals the possibility of having a maximum drill depth the o water table of about 38 m. The results obtained from the pumping test and well logginwereas used to estimate the transmissivity value of T = 0.0722 m2/min, storativity S = 0.00063, specific capacity of the well = 0.39 m2/min and hydraulic conductivity, K= 8.5 m/day while the result from the grain size analysis gave hydraulic conductivity as Kmin= 12.96 m/d to Kmax = 26.96 m/d respectively. Thus, these results indicate that the aquifer is capable of proda ucing sufficient amount of water for both domestic and industrial purposes for the people in the area.
Keywords: grain size; hydraulic conductivity; pumping test; resistivity; storativity